Data on vermicompost effect on the uptake of cadmium from soil by the roots of radish (Raphanus sativus) - Ahmad Zarei; Hassan Reza Rokni (MethodsX, 2024)
Cadmium is a common environmental heavy metal that is very toxic and carcinogenic for human and other flora and fauna. Therefore, this study is aimed to evaluate the fisibility of vermicompost fertilizer for cadmium uptake from soil by the root of radish (Raphanus sativus). For the purpose of the study, four different ratios of one case control, 1 per 1, 1 per 4, 2 per 4, 3 per 4 vermicompost fertilizer per soil with 0, 50000 and 100000 µg/L cadmium concentrations was evaluated. Cadmium in the samples was measured using an Atomic Absorption Spectroscopy (AAS). The results showed that the minimum uptake of cadmium by the plant was observed for 3 per 4 ratio of fertilizer per soil. In addition, results revealed that highest growth rate of Raphanus sativus roots occurred in maximum ratio of fertilizer per soil usage (3 per 4). This study showed that vermicompost as a organic fertilizer has a good ability to adsorb cadmium metal from soil. Therfore, vermicompost application can be considered as an inexpensive natural adsorbent in arable land contaminated with cadmium. • Heavy metals are very toxic and carcinogenic to human and animals. • Adding organic fertilizer to the soil increases the absorption of heavy metal (cadmium) in the soil and prevents it from entering the food chain. • The relationship between the concentration of cadmium absorbed by the tuber of radish plant and the percentage of vermicompost added to the soil is presented.